2012
DOI: 10.1038/mp.2011.179
|View full text |Cite
|
Sign up to set email alerts
|

Absence of evidence for bornavirus infection in schizophrenia, bipolar disorder and major depressive disorder

Abstract: In 1983, reports of antibodies in subjects with major depressive disorder to an as-yet uncharacterized infectious agent associated with meningoencephalitis in horses and sheep led to the molecular cloning of the genome of a novel, negative-stranded neurotropic virus, Borna disease virus (BDV).1,2 This advance enabled the development of new diagnostic assays including in situ hybridization, PCR and serology based on recombinant proteins. Since these assays were first implemented in 1990 more than 80 studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 38 publications
0
58
0
6
Order By: Relevance
“…Although Borna disease virus (BDV) is a prototypical mammalian bornavirus that causes neurobehavioral disorders in rodents (1), the association between BDV and human psychiatric disorders remains controversial (2). Recently, bornaviruses related to BDV were discovered in birds (i.e., avian bornaviruses) (3).…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%
See 1 more Smart Citation
“…Although Borna disease virus (BDV) is a prototypical mammalian bornavirus that causes neurobehavioral disorders in rodents (1), the association between BDV and human psychiatric disorders remains controversial (2). Recently, bornaviruses related to BDV were discovered in birds (i.e., avian bornaviruses) (3).…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%
“…However, inter-laboratory variations in assessing epidemiological assay results have led to inconsistent findings regarding the bornavirus prevalence (5). Overcoming this situation is the first step of reevaluation of bornavirus surveys; therefore, we designed a diagnostic procedure for evaluating bornavirus epidemiology as follows: first, the presence of BDV-reactive antibodies is evaluated by using an indirect immunofluorescence assay (IFA), the most reliable assay for detecting these antibodies (2,5). Second, BDV-reactive samples are evaluated to confirm the presence of antibodies against linear and conformational BDV epitopes by using Western blotting (WB) and a radioligand assay (RLA), respectively (6).…”
Section: Communicated By Masayuki Saijomentioning
confidence: 99%
“…The situation is even more complicated by the facts that no consensus exists on the method that should be used for BDV diagnosis (Wolff et al and that, based on sequence identity, many PCR results and even virus isolation from human peripheral blood cells have been suspected to have arisen from contamination by a control strain (Lieb et al, 1997;Schwemmle et al, 1999;Planz et al, 2003;reviewed by Sauder et al, 2002;Dürrwald et al, 2006b). A recent study using extremely tight criteria for BDV positivity found neither BDV RNA nor verifiable BDV antibodies in the blood samples of Californian psychiatric patients (Hornig et al, 2012).…”
Section: 'Human Bd'?mentioning
confidence: 99%
“…3 To evaluate whether such hormonal, immunological or neuropsychiatric disorders were associated with a persistent viral infection(s) required an armamentarium of novel and sophisticated approaches and techniques to uncover viral genes and/or viral gene products, and discriminate those findings from normal host genes and their products. This issue's paper from Ian Lipkin's laboratory, 'Absence of evidence for bornavirus infection in schizophrenia, bipolar disorder and major depressive disorder,' by Hornig et al 4 displays the usage of such an approach and the controls required to critically define or refute that a pathogen is the cause of a chronic psychiatric disorder.…”
mentioning
confidence: 99%